The Impact of Using English Short Stories in Building Students’ Characters - Salsabila, Nurul; Talib, Ahmad; Sofyan, Ryan Rayhana (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This study aims to determine the impact of using English short stories in building Students’ characters. It employs a qualitative research method with a qualitative descriptive design involving 7 students in the third grade of SMA Negeri 3 Makassar. Data collection techniques include observation, interviews, and documentation. The results of this research found that the study reveals five impacts on students’ characters. The impacts are, students’ behavior that lead to positive behavior, increasing students’ empathy and responsibility character, help students prevent the negative traits, and the last one is students find that there are positive impacts of using English short stories including, increasing language skills, increasing the interest of literacy, and also there is positive character formation in students.   Keywords— Factors, Students' Understanding, Daily English Vocabulary.